Implementasi Struktur Data Queue pada Sistem Antrian di Puskestren Salafiyah Safi’iyah - Alsunil Arobiy; Abd Ghofur; Ach Yusril Ihza Mahendra; Ainur Yakin (Jurnal Ilmu Komputer dan Informatika | E-ISSN : 3063-9026, 2026)
Effective healthcare services require a queue management system that can organize service order systematically to minimize patient waiting time. At Puskestren Salafiyah Syafi'iyah, the queuing process is still carried out in a simple manner, which has the potential to cause disorder, service delays, and errors in calling patients. This study aims to implement the Queue data structure as the basis for managing the patient queuing system in order to make the service process more organized, efficient, and fair. The research employs a descriptive approach by analyzing the patient service workflow and applying the First In First Out (FIFO) concept to the queuing system. The implementation of the Queue data structure enables patients who arrive first to receive service first according to their order of arrival. The results indicate that the implementation of the Queue data structure improves the organization of the queuing process, facilitates patient data management, reduces the potential for errors in calling patients, and enhances the efficiency of healthcare services at Puskestren Salafiyah Syafi'iyah. Therefore, the implementation of the Queue data structure can serve as an effective solution to support a more optimal healthcare service system.